Aspects of Taboos and Euphemisms in Women’s Language - Hysi, Eglantina (Richtmann Publishing, 2011)
This paper provides insight into some of the research findings regarding two main aspects of women’s language, namely taboosand euphemisms. The main aim is to reveal topics that are considered as taboos, and the linguistic devices that women employ to expressthem. Exploring the motives that have given way to the creation of euphemisms we reached the conclusion that fear that people have ofsupernatural powers, superstitions and even the concern that we can cause offence to other human beings if we use a direct language,prevail among other reasons that account for their use. Furthermore, we will focus on the main areas that make a fertile ground forproducing many euphemisms. We will be introduced to the lexicon of disease, death, sex and tabooed body-parts. The various wayseuphemisms are conceptualized reflect directly the mindset and mentality of the community that uses them. Undoubtedly, euphemismsrepresent a wealth of vocabulary in oral culture. Thus, this topic is of a great interest for lexicographers, linguists and literaticians.